Islamism in the Post-Arab Spring world (American Journal of Islam and Society, 2015)
Istanbul Think-House (IDE), a self-supported independent research center thatpromotes the free circulation of ideas, analyzed “Islamism in the Post-ArabSpring World” during its October 24-26, 2014, international conference. IstanbulUniversity’s Political Science Faculty Alumni Association and the Associationfor Human Rights and Solidarity with the Oppressed (MAZLUMDER)hosted the event on their premises.In his opening remarks on Friday morning, conference co-chair and IDE’sgeneral coordinator Halil Ibrahim Yenigun (Istanbul Commerce University)introduced IDE and explained its vision of (1) producing and circulating ideaswithout depending on big capital and political power centers and (2) concentratingsolely on the good of humanity, especially that of the subaltern. IDE isthe outgrowth of national conferences on Islamism held during 2012-13, thefirst event of which had sparked an almost year-long debate in Turkey aboutthe revival of Islamism.The morning panel, “New Islamisms,” dealt with with important theoreticalarguments. Gökhan Sümer (University of Essex) began with a central debateon how to reconcile the constitutional system and the Shari‘ah bybroaching such questions as to whether democratic constitutions ensuring thebasic rights and freedoms could have been passed after the Arab Spring andwhat is Islam’s normative status in these new constitutions. He said that such ...